Analisa Faktor yang Mempengaruhi Teknik Pengolahan Sampah Medis Berdasarkan Permenkes RI Nomor 18 Tahun 2020 di Puskesmas Koto Lolo Kota Sungai Penuh Tahun 2025 - Sri Yulianti; Subang Aini Nasution; Dewi Riastawaty (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aimed to analyze the factors influencing solid medical waste management practices based on the Regulation of the Indonesian Minister of Health Number 18 of 2020 at Koto Lolo Primary Health Center, Sungai Penuh City, in 2025. This study employed a quantitative descriptive-analytic approach with a cross-sectional design. The research was conducted in September 2025 involving all 80 healthcare personnel responsible for medical waste management. A total sampling technique was applied, in which all eligible personnel were included as study respondents. Data were collected through structured questionnaires, observations, and documentation, consisting of both primary and secondary data. Data analysis included univariate analysis to describe respondents' characteristics and study variables, followed by bivariate analysis to examine the relationships between independent variables and medical waste management practices. The findings revealed a significant association between knowledge and solid medical waste management practices in accordance with the Regulation of the Indonesian Minister of Health Number 18 of 2020 (p=0.001). Facilities and infrastructure were also significantly associated with proper medical waste management practices (p=0.002), while healthcare workers' behavior demonstrated a significant relationship with waste management implementation (p=0.003). The study concludes that knowledge, the availability of facilities and infrastructure, and healthcare workers' behavior are significant determinants of appropriate solid medical waste management practices.